Between memory and erasure: Zézé Gamboa’s O Grande Kilapy and the legacy of portuguese colonialism - Stewart, Katy (2016)
While the 40th anniversary of the “fall of the Portuguese Empire” has provoked fresh critical approaches to the colonial legacy within Portugal, much less attention has been paid to how memories of colonialism are being reconfigured within contemporary lusophone African cultural production. The films of Angolan director Zézé Gamboa have thus far received very little academic attention, particularly his most recent feature, O Grande Kilapy (2012) (The Great Kilapy), which is the focus of this article. Yet the film demonstrates the urgency of redeeming memory in a postcolonial society, and how the power to silence such memories is embedded in the geopolitical structures of the lusophone world. This article will demonstrate how Gamboa decolonises the imagination by reclaiming memories and reframing history, but also how this very redemption and transmission of memories is limited by production and distribution constraints imposed upon the film itself, defined by configurations of power within the postcolonial lusophone space. Therefore, while recognising the importance of the archive for memory, as Pierre Nora proposes, this article will posit that alternative strategies, present within O Grande Kilapy, such as the oral transmission of stories, are essential for working around such constraints.